-34=8x-5(1-7x)

Simple and best practice solution for -34=8x-5(1-7x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -34=8x-5(1-7x) equation:


Simplifying
-34 = 8x + -5(1 + -7x)
-34 = 8x + (1 * -5 + -7x * -5)
-34 = 8x + (-5 + 35x)

Reorder the terms:
-34 = -5 + 8x + 35x

Combine like terms: 8x + 35x = 43x
-34 = -5 + 43x

Solving
-34 = -5 + 43x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-43x' to each side of the equation.
-34 + -43x = -5 + 43x + -43x

Combine like terms: 43x + -43x = 0
-34 + -43x = -5 + 0
-34 + -43x = -5

Add '34' to each side of the equation.
-34 + 34 + -43x = -5 + 34

Combine like terms: -34 + 34 = 0
0 + -43x = -5 + 34
-43x = -5 + 34

Combine like terms: -5 + 34 = 29
-43x = 29

Divide each side by '-43'.
x = -0.6744186047

Simplifying
x = -0.6744186047

See similar equations:

| 4j=5j-7 | | 4x+8=12x-12 | | 3g=-7+4g | | 9(t-5)+6t=5(3t+4)-10 | | m=-0.4n+28 | | y+y-y-y+y-1=18 | | -93-4v=-10v+3 | | 2x^4-9x^2-16x=0 | | 3h+3h-6h+2j-2=12 | | 2x^4-9x^2-16=0 | | 18j+2j-10j-5j-4j=16 | | 18j+2j-10-5j-4j=16 | | 13p-6p-5p=18 | | 9t+(3f)t+13= | | 27-×/4=x/5 | | 4+7x-3=9x+13-6x | | 6j+-2j+14j-7j+-9n-(-19)=-15 | | m(a+5)=Kfora | | -0.1x^2-x+31=0.1x^2+2x+11 | | 6j+-2j+14j-7j+-9-(-19)=-15 | | 0.2x^2+x-20=0 | | 6j+-2j+14j-7j+(-19)=-15 | | 6j+2j+14j-7j+(-19)=-15 | | r-r+5r-2r=9 | | -5c+14c+-7=11 | | 5b-19b-(-20b)-(-14)=-10 | | 32+0.90m=2(31+0.30m) | | 20m-10m+2m-8m+2m=6 | | 5u+4u-6u-u=12 | | n^2-n-480=0 | | log(base)2(x^2-3x-66)=2 | | 20n-12n+-9n=8 |

Equations solver categories